Cool early Albian climates; new data from Argentina - Pirrie, D. (2004)
Previous studies on the stable isotope geochemistry of dimitobelid belemnites from Antarctica and Australia indicated cool climatic conditions during the early Albian in the shelf seas around the Gondwanan margin. In this paper new analyses from diagenetically unaltered specimens of Dimitobelus cf. stimulus from early Albian deposits of the Rio Mayer Formation of Lago San Martin, southern Argentina are presented. Oxygen isotope values for diagenetically least altered samples give values ranging between d18O C0.07 and C0.96 vPDB, which equate to a mean palaeotemperature of 9.5 (C (assuming dw of 1.2& SMOW). These data are consistent with a model of cool early Albian shelf seas in the Southern Hemisphere.